Radiolysis of N2O:CO2 ice by heavy ions: simulation of cosmic ray effects. Issue 4 (27th June 2018) - Pereira, R C; de Barros, A L F; Fulvio, D; Boduch, P; Rothard, H; da Silveira, E F
ABSTRACT: N-O-bearing molecules are considered to be important primary molecules of complex and prebiotic species in space, and therefore an understanding of the N-O chemistry is a fundamental step in linking the origin and evolution of prebiotic species to the evolution of interstellar and Solar System ices. With this in mind, we have started an extensive program of laboratory work to study and understand the effects of cosmic radiation on N-O-bearing molecules in space. Carbon dioxide (CO2 ) and nitrous oxide (N2 O) are volatile molecules found in the Solar System and in the interstellar medium. Thus it is expected that both molecular species may freeze-out on dust grains and the surface of Solar System bodies and be exposed to cosmic radiation. The objective of the present work is to obtain an experimental analysis of the ion irradiation effects in an N2 O:CO2 (1:2) ice mixture, at 11 K, when the mixture is irradiated by 90-MeV 136 Xe 23 + . Fourier-transformed infrared spectroscopy (FTIR) was the method of analysis used for this purpose. Eight product molecular species have been observed: CO, CO3, NO, NO3, N2 O2, N2 O3, N2 O4 and O3 ; C−N compounds were not observed. The chemical evolution of the new molecules formed in the sample was followed by estimating the column densities of the primary molecule and products as a function of the beam fluence. This procedure allows the determination of their formation and dissociation cross-sections. The destruction cross-section of N2 O is approximately twice that of CO2, which results in relatively large quantities of N, O, N2 and NO molecules in the ice.